Preclinical Differentiation between Apparently Safe and Potentially Hepatotoxic Applications of TRAIL Either Alone or in Combination with Chemotherapeutic Drugs - Tom M. Ganten; Ronald Koschny; Jaromir Sykora; Henning Schulze‐Bergkamen; Peter Büchler; Tobias L. Haas; Manuela B. Schader; Andreas Untergasser; Wolfgang Stremmel; Henning Walczak (2006)
Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL/Apo2L) exhibits potent antitumor activity on systemic administration in nonhuman primates without deleterious side effects for normal tissue. However, there is a controversy about the potential toxicity of TRAIL on human hepatocytes. The use of different recombinant TRAIL forms only partially explains the contradicting reports on TRAIL sensitivity in primary human hepatocytes (PHH).To clarify this issue, we comprehensively tested four different recombinant forms of TRAIL for their apoptosis-inducing capacity on PHH obtained from a total of 55 human livers between day 1 and day 8 of in vitro culture.One day after single-cell isolation, all but one recombinant form of TRAIL [i.e., an untagged form of TRAIL (TRAIL.0)] induced apoptosis in PHH. Apoptosis induction by TRAIL in these cells could only be fully inhibited by concomitant blockade of TRAIL receptor 1 and TRAIL receptor 2. At day 4 of in vitro culture, when surrogate markers indicated optimal hepatocyte in vitro function, only high doses of cross-linked FLAG-TRAIL killed PHH whereas the other three recombinant TRAIL forms did not. Strikingly, cotreatment of day 4 PHH with cisplatin sensitized for TRAIL-induced apoptosis whereas 5-fluorouracil, etoposide, gemcitabine, irinotecan, or oxaliplatin, which are commonly used in the treatment of gastrointestinal cancers, did not.Our data show that whereas TRAIL alone or together with selected chemotherapeutic drugs seems to be safe, the combination of TRAIL with cisplatin is toxic to PHH.